Metryki w uczeniu ekonomii - Maciuk, Arkadiusz (Metrics in Teaching of Economics, 2006)
Nowadays there is a strong pressure to reduce the program of maths during the first year of economy studies. The Autor lists several reasons why teaching metric space should be continued or moreover intensified.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1117, s. 106-113